2010
DOI: 10.1089/scd.2009.0286
|View full text |Cite
|
Sign up to set email alerts
|

Reserves, Functional, Immunoregulatory, and Cytogenetic Properties of Bone Marrow Mesenchymal Stem Cells in Patients with Myelodysplastic Syndromes

Abstract: Defective hematopoiesis supporting capacity of bone marrow (BM) stroma has been implicated in the pathophysiology of myelodysplastic syndromes (MDS). The aim of this study is to explore whether the BM stroma progenitors, namely the mesenchymal stem cells (MSCs), are primarily affected in MDS by evaluating the reserves, the functional properties, as well as the cytogenetic characteristics, in comparison to BM hematopoietic cells, in patients with de novo MDS (n = 13). The number, differentiation potential towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 48 publications
10
77
1
5
Order By: Relevance
“…The immune-modulatory properties, cytokine secretion and cytogenetic profiles of MSCs have shown to be altered in MDS [16][17][18][19][20][21][22][23]. The groups which claim the genetic susceptibility of MSCs argue on the potential involvement of these cells in the pathogenesis of the disease [16][17][18][19][20][21][22].…”
Section: The Role Of Bone Marrow Stroma and Mesenchymal Stem Cells Inmentioning
confidence: 99%
See 4 more Smart Citations
“…The immune-modulatory properties, cytokine secretion and cytogenetic profiles of MSCs have shown to be altered in MDS [16][17][18][19][20][21][22][23]. The groups which claim the genetic susceptibility of MSCs argue on the potential involvement of these cells in the pathogenesis of the disease [16][17][18][19][20][21][22].…”
Section: The Role Of Bone Marrow Stroma and Mesenchymal Stem Cells Inmentioning
confidence: 99%
“…normal with respect to the ability of sustaining the growth of CD34 + cells in co-cultures and secretion of normal levels of cytokines and growth factors (TNF-α, IL-6, stem cell factor, GM-CSF, VEGF, collagen and fibronectin) [24,25] some other studies show that MDS-MSCs are unable to support hematopoiesis [16][17][18][19][20][21][22][23]. Further, some studies have shown that the MSCs of MDS secrete increased levels of certain cytokines such as TNFα, IL-6, IFN-γ and angiogenic cytokines [17,18].…”
Section: Journal Of Molecular and Genetic Medicinementioning
confidence: 99%
See 3 more Smart Citations